Busca de plantas medicinais da Renisus através da triagem virtual para atividade anti-Helicobacter pylori - Mendes, Campili (2024)
Helicobacter pylori (H. pylori) is a Gram-negative bacterium that infects and colonizes the gastric mucosa of around half of the world's population, and its prevalence is higher in developing countries, reaching up to 90%. H. pylori infection triggers a series of diseases ranging from gastritis and ulcers to gastric cancer, which is the fifth most common cancer in humans. The bacterium is considered a group I carcinogen, according to the World Health Organization, and is included in the list of high-priority bacteria in the development of new drugs. In this context, medicinal plants and their phytocompounds are valuable shortcuts for discovering new, safer antibiotics with reduced adverse effects. In this context, the aim of this study was to select species from the National List of Medicinal Plants of Interest to the Unified Health System (Renisus) with potential anti-H. pylori activity, firstly through a bibliographic survey, followed by the creation of a phytochemical database and evaluation in an activity prediction model using PASS (Prediction of Activity Spectra for Substances), Tanimoto Similarity and, finally, in vitro evaluation. Once the species had been selected, the chemical profile was determined by high-resolution mass spectrometry (ESI-FT-ICR/MS - Electrospray Ionization-Fourier Transform Ion Cyclotron Resonance/Mass spectrometry) and liquid chromatography coupled to mass spectrometry (LC-MS - Liquid chromatography-mass spectrometry), and the compounds identified were analyzed by molecular docking in the active site of the bacterial target. After the bibliographic survey, 4 species were selected based on studies against gastritis and ulcers, but without studies against H. pylori, namely: Bauhinia forficata, Jatropha gossypiifolia, Sonalum paniculatum and Vernonia condensata. In the virtual screening, using PASS, the species J. gossypiifolia showed more compounds with the possibility of being active for 02 targets of action: the enzymes urease and fumarate reductase. Tanimoto's similarity analysis used standard inhibitors of these targets, acetohydroxamic acid and licochalcone A, respectively, to which the compounds present in J. gossypiifolia showed better similarity compared to the other species. To validate the virtual screening, in vitro tests were carried out to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the extracts of the 4 selected species, with J. gossypiifolia showing the best results with a MIC of 64 µg/mL and MBC of 128 µg/mL. An in vitro urease inhibition test was also carried out, but none of the species selected showed satisfactory concentration/response activity against the enzyme. Among the compounds suggested by ESI-FT-ICR/MS and LC-MS, C-glucosilated flavonoids such as 3-genistein-8-C-glycoside and derivatives of luteolin and apigenin had the potential to interact with the active site of furamate reductase, hydrogen bonding with Arg404. In addition, 3-genistein-8-C-glucoside and luteolin 7-O-glucoside have five hydrogen bonds with amino acid residues, which is similar to the interaction of the fumaric acid ligand in the enzyme's active site. In view of the above, virtual screening proved to be a valuable tool in this study, and J. gossypiifolia showed promising activity and could represent an alternative source of compounds for treating H. pylori and preventing its harmful effects